Perbandingan Nilai Daya Dukung Fondasi Dangkal Menurut Metode Terzaghi Dan Meyerhof - Hisam Asngari; Suradji Gandi; Fatma Sarie (Media Ilmiah Teknik Sipil, 2021)
In every building, a foundation is needed as a strong and sturdy building foundation. The foundation aims to support the building and pass the load on the building above it to a layer of soil that is strong enough to have a bearing capacity. To calculate the carrying capacity of the soil, there are many formulas that can be used. The results of each of these formulas produce different carrying capacity values. The purpose of this study is to calculate and analyze the bearing capacity of shallow foundations from the results of hand boring with the Terzaghi and Meyerhof methods. The results showed that the carrying capacity of the shallow foundation soil in the Terzaghi method was smaller than that of the Meyerhof method. The value of the terzaghi method is 353,443 KN /m2, while the Meyerhof method has increased by 70,094%, with a value of 601,185 KN /m2.